Perspectives on intimate partner violence in Swaziland amongst 18–29-year-old men undergoing medical circumcision - Brear, M.; Bessarab, Dawn (Routledge, 2011)
Intimate partner violence (IPV) is perceived as a major contributor to HIV transmission in Swaziland. This exploratory study aimed to develop a culturally-specific understanding of men's perspectives of IPV. Focus group methods were used to gather information from 45 young urban Swazi men who had undergone medical male circumcision. A thematic analysis was conducted focussing on the manifestations of IPV and socio-cultural and economic factors which underpin, circumstances which trigger and social responses to IPV. The study identified numerous forms of economic, physical, emotional and sexual abuse that study participants perceived men used to control women in Swaziland. Many of these directly increased a woman's risk of HIV infection, including knowingly infecting a woman with HIV and intentionally impregnating a woman, a practice that has not previously been highlighted in the literature. Aspects of Swazi culture that may facilitate these particular forms of abuse are discussed. This study highlights the need for the gender issues which underpin IPV to be addressed in HIV prevention in Swaziland and for the development of an informed understanding of how and why IPV occurs in the Swazi context.